Упростите выражение (х+3)(х2-3х+9)-х(х-4)(х+4)-27 и вычислите его значение при х=-8.

198219821982 198219821982    2   09.12.2020 03:11    2

Ответы
NIKTENKOELENA70 NIKTENKOELENA70  09.12.2020 06:00

a³ + b³ = (a + b)(a² - ab + b²)

a² - b² = (a - b)(a + b)

(х+3)(х²-3х+9)-х(х-4)(х+4)-27 = x² + 3³ - x(x² - 4²) - 27 = x³ + 27 - x³ + 16x - 27 = 16x

x = -8

16x = 16*(-8) = -128

ПОКАЗАТЬ ОТВЕТЫ
рома1344 рома1344  09.12.2020 06:00

ответ:-128

Объяснение:

Это правильно, я из Альт))

ПОКАЗАТЬ ОТВЕТЫ